Explanation :
Given that
$ \mathrm p\left(\mathrm P\right)=\frac14\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;...(1) $
$ \mathrm p\left(\mathrm P\vert\mathrm Q\right)=\frac12\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;...(2) $
$ \mathrm p\left(\mathrm Q\vert\mathrm P\right)=\frac13\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;...(3) $
$ p\left(\overline{\mathit P}\mathit\vert\overline{\mathit Q}\right)=? $
First solve for $ \mathrm p\left(\mathrm Q\right) $ and $ \mathrm p\left(\mathrm P\cap\mathrm Q\right) $ from equation (2) and (3) as follows:
From equation (2)
$ \mathrm p\left(\mathrm P\vert\mathrm Q\right)=\frac{p\left(\mathit P\mathit\bigcap\mathit Q\right)}{p\left(\mathrm Q\right)}=\frac12\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;...(4) $
From equation (3)
$ \mathrm p\left(\mathrm Q\vert\mathrm P\right)=\frac{p\left(\mathit P\mathit\bigcap\mathit Q\right)}{p\left(P\right)}=\frac13 $
$ \Rightarrow\mathrm p\left(\mathrm P\cap\mathrm Q\right)=\frac13\times p\left(\mathit P\right)=\frac13\times\frac14=\frac1{12} $
Now substitute in equation (4) and get
$ \mathrm p\left(\mathrm Q\right)=\frac{\mathit p\left(\mathit P\mathit\bigcap\mathit Q\right)}{\mathit1\mathit/\mathit2}=\frac{1/12}{1/2}=\frac2{12}=\frac16 $
So now we have
$ \begin{array}{l}\mathrm p\left(\mathrm P\right)=\frac14\\\mathrm p\left(\mathrm Q\right)=\frac16\end{array} $
and $ \mathrm p\left(\mathrm P\cap\mathrm Q\right)=\frac1{12} $
we need to find
$ \begin{array}{l}\;\;\;\;\;\;p\left(\overline P\cap\overline Q\right)=\frac{p\left(\overline P\cap\overline Q\right)}{p\left(\overline Q\right)}\\=\frac{1-\left(P\cup Q\right)}{1-p\left(Q\right)}=1-\frac{\left[p\left(P\right)+p\left(Q\right)-p\left(P\cap Q\right)\right]}{1-p\left(Q\right)}\\\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;=\frac{1-\left[{\displaystyle\frac14}+{\displaystyle\frac16}-{\displaystyle\frac1{12}}\right]}{1-{\displaystyle\frac16}}=\frac{\displaystyle\frac23}{\displaystyle\frac56}=\frac45\end{array} $
So, $ p\left(\overline P\vert\overline Q\right)=\frac45 $